Techniques to select site of insertion for a peripheral intravenous catheter with vessel locating devices using light, sounds or tactile actions (or palpations). Issue 7 (29th January 2021) - Higgins, Niall; Iu, Peter; Carr, Peter; Ware, Robert; Van Zundert, André
Abstract: Background: Approximately 80% of patients admitted to acute hospitals have at least one peripheral intravenous catheter inserted during their admission, for the administration of fluids and medicines, and/or diagnostic tests, so the failure rate is concerning. New technology may decrease these rates even when used by inexperienced inserters. The choice of insertion site for an intravenous catheter is a known predictor of catheter failure. Therefore, the objective for this study was to evaluate the utility of vessel locating devices for novice clinicians to select catheter insertion sites in the forearm. Methods: An inter‐subject incomplete counterbalanced research design was employed with healthy volunteers. Novice clinicians used either a vessel locating device using light or sound waves or they used palpation to identify relatively superficial veins in the forearm. This was compared to site selection performed by an expert clinician using palpation method only. Measurements of differences were analysed from photos of chosen sites. Bland–Altman agreement analysis was used to plot novice expert agreement. The STROBE checklist was followed in reporting this study (Techniques to select site of insertion for a peripheral intravenous catheter with vessel locating devices (Appendix S1)). Results: A total of 32 novice clinicians used three vessel locating devices and a palpation technique. Novice clinicians did not choose more veins for optimum catheter placement when assisted with vessel locating devices compared to palpation techniques. All methods had a similar mean difference between novice and expert measurements and a similar percentage difference in distance from the expert choice. Bland–Altman agreement analysis did not identify any advantage for the novice with vessel locating devices over palpation. Conclusion: Vessel locating devices do not enhance the ability of novice clinicians any greater than palpation when selecting suitable forearm veins. If vessel locating device approaches are to be adopted in clinical practice to support better insertion outcomes then current PIVC teaching techniques should include structured vessel locating devices theory and practice. Relevance to clinical practice: Successful insertion of a peripheral intravenous catheter (PIVC) on the first attempt is a challenging procedure for nurses. Careful consideration of the selected site of insertion could modify this risk factor for catheter failure. The choice of PIVC insertion site by a novice clinician compared to an expert does not necessarily improve with the use of vein locating technology. While there is a range of technological devices available to assist with locating vessels, there needs to be more emphasis from educators on how to select an appropriate insertion site for intravenous therapy.